(untitled) (مجلة البيان العلمية, 2023)
Zea mays L. tolerated drought stress up to 150 % water field capacity (F.C.).Water stress (waterlogging condition) decreased maize growth parameters especially at high drought stress level 150 % water field capacity (F.C.% ) . Marine algae extracts as biofertilizers and salicylic acid foliar application increased height plants and leaf-area at 200 % water field capacity compared with absolute control treatment . Marine algae extracts as biofertilizers and salicylic acid foliar application increased maize dry shoot-mass 200 % field capacity as compared with control plant . Marine algae extracts as biofertilizers and salicylic acid foliar application increased maize chlorophyll a, b and carotenoids at 100 % field capacity as compared with control plant . Marine algae extracts as biofertilizers and salicylic acid foliar application highly significant increased shoot soluble carbohydrates up to 200 % field capacity as compared with the control plant. Calcium, Potassium and Phosphorus accumulation was decreased by decreasing water field-capacity in maize plants of control-plant.Phosphorus accumulation was increased by Marine algae extracts as biofertilizers and salicylic acid foliar application in the maize plants and recorded increases compared with control, respectively.Salicylic acid application with or without marine algae extracts as biofertilizers reported increases in proline in the shoot system .Hydrogen peroxide H2O2 generation was increased in flooding treatments and increases at 150 and 200 % field-capacity level, respectively. marine algae extracts as biofertilizers or salicylic acid reduced H2O2 concentration as compared to control plant.